Probing Majorana neutrinos in the regime of the normal mass hierarchy - Biller, S (2013)
An approach to developing a feasible neutrinoless double beta decay experiment capable of probing Majorana masses in the regime of the nondegenerate normal neutrino mass hierarchy is proposed. For such an experiment, this study suggests that Te130 is likely the best choice of candidate isotope and that metal-loaded liquid scintillator likely represents the best choice of detector technology. An evaluation of the required loading, scintillator properties and detector configuration is presented. While further development of Te-loaded liquid scintillator is required, recent progress in this area suggests that this task may not be insurmountable. This could open the door for a future experiment of unparalleled sensitivity that might be accommodated in a volume of the order of 10-20 kilotons. To the best of our knowledge, this is the first time that a potentially practical experimental approach to exploring Majorana neutrino masses in the nondegenerate normal hierarchy has been suggested.